What We Learn From Innovation Failure A Review of Clean Water Postpaid Service in Remote Island Indonesia Using Sea Water Reverse Osmosis (SWRO) Technology - Rendi Febrianda; Nur Laili (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2020)
Every project from government, should be or must be delivering a great mission, especially for undeveloped areas. But the fact is, there were plenty of them failed to sustain then became out of order. This article uncovers the reason behind one of central government project supplying clean water to remote area that has a big tendency of failing to sustain its service. Using formulated factors of achieving the sustainability of clean water service as the framework, and social innovation approach as the tool of analysis, the result indicates that the service started to maintain its effective demand onerously due to dealing with the sociocultural of the users. What was missing from the system of the project for delivering the service and what solution must be taken will be discussed on this article.Keywords: sustainability, clean water service, social innovation, sociocultural